2022
DOI: 10.7759/cureus.32545
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Ascariasis Involvement in Gallbladder Disease: A Systematic Review of Case Reports

Abstract: Ascaris lumbricoides is the most common type of helminth infection in humans. It affects more than one billion of the world's population. Children living in developing nations are prone to ascariasis, presenting with obstructive biliary illnesses. Migration of Ascaris worms through the major duodenal papilla to the hepatobiliary system leads to symptoms of biliary colic and complications along the biliary tree. In April 2022, we performed a systematic review of case reports to identify and examine cases of gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…If a child presents with biliary colic and/or jaundice, it is important to consider other potential differential diagnoses such as cholelithiasis, cholecystitis, biliary tract stricture, and extrinsic compression of the bile ducts. 6 , 7 The diagnosis of hepatobiliary ascariasis is reached through clinical examination and radiologic investigation. Ultrasound is the preferred investigative modality with excellent sensitivity which remarkably increased the diagnosis of biliary ascariasis.…”
Section: Discussionmentioning
confidence: 99%
“…If a child presents with biliary colic and/or jaundice, it is important to consider other potential differential diagnoses such as cholelithiasis, cholecystitis, biliary tract stricture, and extrinsic compression of the bile ducts. 6 , 7 The diagnosis of hepatobiliary ascariasis is reached through clinical examination and radiologic investigation. Ultrasound is the preferred investigative modality with excellent sensitivity which remarkably increased the diagnosis of biliary ascariasis.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging in our case showed curvilinear echogenicity of roundworm in the gallbladder and common bile duct with mild dilatation of the common bile duct. Other methods of imaging include endoscopic retrograde cholangiopancreatography, abdominal magnetic resonance cholangiopancreatography, and magnetic resonance imaging (MRI) 5 . Diagnosis is confirmed by stool examination for ova or adult worms.…”
Section: Discussionmentioning
confidence: 99%
“…But, in the absence of isolation of the microorganism, typical imaging findings can be helpful 4 . Other laboratory findings include leukocytosis, elevated liver enzymes, elevated C-reactive protein, eosinophilia, elevated serum bilirubin, elevated erythrocyte sedimentation rate, raised amylase and lipase, etc 5 . However, in our study the lab investigations showed mildly increased total and direct bilirubin, mildly elevated aminotransferases, elevated absolute eosinophil count, and normal total serum bile acid levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 For patients that do not respond to conservative therapy, endoscopic and open surgical methods are best. 25 …”
Section: Discussionmentioning
confidence: 99%